Impact of different agricultural biomass residues on the performance of continuous solar-steam gasification - Srirat Chuayboon; Stéphane Abanades (Industrial Crops and Products, 2025)
Solar-driven biomass gasification represents a promising avenue for sustainable carbon-neutral fuel production. Nevertheless, the types of raw biomass materials play a vital role in continuous solar gasification performance. In this study, continuous solar-steam gasification with various agricultural crop residues was experimentally carried out in a 1.5 kW th solar gasifier to investigate the influence of biomass types on performance and efficiency under different operating temperatures up to 1400 °C. Seven agricultural residues were used as feedstocks, including oil palm wastes (palm mesocarp fiber, palm empty fruit bunch, and palm kernel shell), bagasse, betel nut, coconut fiber, and rice husks. Results demonstrated that the system can effectively perform with all biomass types with high-quantity and high-quality syngas production. The process revealed exceptional performance and efficiency, including the total maximum syngas yield range of 67.9–81.5 mmol/g dry biomass , reaching 81.4–95.2 % of the theoretical total syngas yields, maximum energy upgrade factor (1.05–1.35), reaching 94.2–97.3 % of the theoretical values, and maximum carbon conversion (87.2–96.9 %). The feedstock types showed a significant influence on gasification outcomes. Palm oil empty fruit bunch, betel nut, and palm mesocarp fiber were promising candidates for solar gasification with their high volatile content and significant decomposition potential, followed by coconut fiber and bagasse. Nevertheless, palm kernel shell and rice husk were found to be unsuitable biomasses for continuous solar-steam gasification because of the issues of reduced gasification activity and reaction rate limitations, due to a high density for palm kernel shell and a high ash content for rice husk. A temperature of 1300 °C was recommended to carry out continuous solar-steam gasification, leading to the maximum solar-to-fuel energy conversion efficiency in the range 13.7–18.9 %. This study provides insights into the influence of agricultural residue types on the solar-steam gasification process, while assisting in the proper biomass residue selection for efficient continuous solar gasification. • Continuous solar steam gasification of agricultural biomass residues was demonstrated. • The solar reactor can accommodate various feedstock types showing process flexibility. • The feedstock type notably influenced the gasification performance and efficiency. • The syngas yield was in the range of 56.9–81.5 mmol/g dry biomass between 1100 and 1400°C. • A temperature of 1300°C led to maximum solar-to-fuel efficiency (13.7–18.9 %).
Keywords: Thermochemical Biomass Conversion Processes; Chemical Looping and Thermochemical Processes; Coal Combustion and Slurry Processing